Investigation into the subjective well-being of older adults via confirmatory factor analysis and analytic hierarchy process—an empirical analysis based on CGSS2021 data - Yingying Chen; Tianrui Cai; Ruiqin Tian (Frontiers in Public Health)
BackgroundThis paper examines the subjective well-being of older adults in China. Based on data from the China General Social Survey (CGSS2021), the agreement levels of 21 questions on the subjective well-being of older adults were extracted and analyzed.MethodsThe 21 questions were categorized into positive and negative factors based on cluster analysis. For the 10 positive factors, the information entropy method was used to determine their weights and calculate the happiness scores of older adults. For the 11 negative factors, the unhappiness scores of older adults were calculated by the confirmatory factor analysis and analytic hierarchy process.ResultsAn average happiness score of 4.499 was obtained, of which the more influential factors were family income, personality control, and the natural environment. An average score of 3.062 was obtained, among them, the more influential factors are health status, family communication and body parts.Conclusions and recommendationsOverall, it shows that the subjective happiness of the Chinese older adults is strong and unhappiness is weak. Then we further find significant differences in the above scores of older adults with different socioeconomic status through one-way ANOVA. Based on the results of the study, we finally proposed targeted recommendations to improve the happiness feelings of older adults, including encouraging communication with family members and improving body parts.